Students commitment to bioethics during the process of clinical training in Dentistry - Lee Muñoz, Ximena; Vergara Núñez, Cristián; Astorga Bustamante, Elizabeth; Hanne Altermatt, Christel (Acta Bioethica, 2013)
This study pretends to understand, through speech analysis, the commitment to bioethics of dentistry students, who participate in the process of clinical training. Through a qualitative methodology the object of study was approached in its natural setting. Data collection was carried out through diverse information sources. The instruments used were documental analysis, observation without participating and semi structure interviews. In order to analyze data, meaningful topics were identified, determining units to record for categorizing information. To understand the processes involved, empirical information is shown by describing tendencies. These describe empirical information using indicators for each category. The analysis builds the meaning of information recorded. It is concluded that communication, trust and responsibility are indicators of scarce development in general. Speech analysis, under the perspective of students, reveals diverse visions about teaching practices related to bioethics commitment, raising the need to reconsider these practices in order to contribute to a professional training of real social commitment.